Genetic polymorphism analysis of 40 Y-chromosomal STR loci in seven populations from South China. (October 2018) - Liu, Changhui; Han, Xiaolong; Min, Yunbing; Liu, Hong; Xu, Quyi; Yang, Xingyi; Huang, Shuqin; Chen, Zucong; Liu, Chao
Highlights: Seven nationalities in south China's Guangxi province were investigated. The efficacy of AGCU Y24 STR and GFS Y24 STR genotyping kits was validated. Except for a shared haplotype between Han and Gin, no others were observed. Abstract: China is a multi-ethnic country. Due to its diverse terrain, many ethnic groups are geographically isolated within China. This phenomenon is especially prevalent in southern China. As Y-STR loci are paternally inherited, they can be used to effectively understand the genetic relationship between different populations and thus aid in forensic science. In this study, forty Y-STR loci were analysed in 2018 unrelated male individuals from the following seven ethnic populations in South China: Yao (n = 147), Zhuang (n = 225), Gelao (n = 156), Miao (n = 186), Maonan (n = 133), Gin (n = 160) and Guangxi Han (n = 1011). Using both AGCU Y24 STR and GFS Y24 STR genotyping kits, a total of 335 alleles and 141 haplotypes of three multi-copy loci were observed in these seven populations. The highest GD value of the 40 Y-STR loci in the overall population was 0.9643 for DYS385a/b, while the lowest was 0.4101 for DYS438. Out of the 2018 samples analysed, 1935 distinct haplotypes and 1858 unique haplotypes were observed. The HD value of the total samples was up to 0.9994 and ranged from a low of 0.9908 in the Yao to a high of 0.9999 in the Han population. We found using population structure analysis that the genetic distance is smaller among the seven southern populations (Guangxi Han, Gelao, Yao, Miao, Zhuang, Jing and Maonan) than the northern populations (Tibetan, Korean, Mongolian, Uygur and Hui). We show that the 40 Y-STRs have a high level of polymorphism in the South China ethnic groups and there is a high degree of differentiation among ethnic groups located in geographically distributed and densely populated areas. These data may provide additional resources for forensic applications and population genetic studies.